Acute Renal Failure and Volume Overload Syndrome Secondary to a Femorofemoral Arteriovenous Fistula Angioplasty in a Kidney Transplant Recipient - Dominique Bertrand; Geoffroy Desbuissons; Nicolas Pallet; Albane Sartorius; Christophe Legendre; Marie-France Mamzer; Rebecca Sberro Soussan (Case Reports in Transplantation)
Experimental and clinical studies analyzing the impact of AVF on cardiovascular and renal parameters, as well as outcomes, in kidney transplant recipients are lacking. On the other hand, it is not known whether AVF ligation after transplantation modifies hemodynamic parameters and kidney function. We report a case of a renal transplant recipient who developed an acute congestive heart failure accompanied by renal failure, which were triggered by femorofemoral AVF angioplasty. Prompt AVF ligation rapidly reversed clinical symptoms and normalized cardiac and renal functions. This paper illustrates the potential deleterious consequences of high-output AVF after kidney transplantation and raises considerations regarding the impact of the fistula on cardiac status and kidney function after kidney transplantation and, consequently, the management AVF after transplantation.